2002
DOI: 10.1097/00000539-200208000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Hepatosplanchnic Oxygenation and Increase of Serum Hyaluronate During Normothermic and Mild Hypothermic Cardiopulmonary Bypass

Abstract: Hepatic sinusoidal endothelial cells (SECs) are pivotal in the regulation of sinusoidal blood flow. This study showed that SEC function might be impaired during and after cardiopulmonary bypass, irrespective of the temperature management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…10 In addition, hypothermia, hemodilution, and hypoperfusion during CPB may be responsible for the morbidity and mortality. 11 Therefore, Hayashida et al 4 recommended off-pump coronary artery bypass (OPCAB) because the use of CPB can be avoided. They reported that none of the three patients with class B cirrhosis undergoing OPCAB died.…”
Section: Resultsmentioning
confidence: 99%
“…10 In addition, hypothermia, hemodilution, and hypoperfusion during CPB may be responsible for the morbidity and mortality. 11 Therefore, Hayashida et al 4 recommended off-pump coronary artery bypass (OPCAB) because the use of CPB can be avoided. They reported that none of the three patients with class B cirrhosis undergoing OPCAB died.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature, bypass mode, and bypass flow may at least in part explain these discrepancies. Increased hepatosplanchnic oxygen consumption and oxygen extraction have been reported during normothermic CPB by some (35,36) but not all (33) authors. In the present study, only a partial extracorporeal circuit without an oxygenator was used; hence, our model may not reflect all the pathophysiologic features of CPB.…”
Section: Discussionmentioning
confidence: 95%
“…Post-CPB hepatic dysfunction may be multifactorial in origin, and many factors related to the cardiac operation can jeopardize the integrity of the liver. Situations such as perioperative hypotension, a low flow state, hypoxemia, formation of free radicals precipitated by the extracorporeal circuit, microembolism, influence of vasopressor agents, and anesthesia may all play an important role in the developing of hepatic failure after cardiac operations [2,24]. It is also possible that derangements in the hepatic blood supply may play a distinct role in the development of post-CPB hepatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence from experimental data and clinical series that CPB can have a profound impact on the hepatosplanchnic region [1]. Specifically, there have been numerous reports of liver function impairment after open-heart surgery, which often occurs irrespective of preoperative hepatic reserve [2]. Hyperbilirubinemia and transient elevation of liver enzymes are a common occurrence after CPB procedures [3,4].…”
Section: Introductionmentioning
confidence: 99%